Deteksi Risiko Tinggi Kehamilan Pada Pelayanan Anc Terpadu di Puskesmas Bangkala Kota Makassar Tahun 2020 - Ekawati, Nur (Jurnal Ilmiah Amanah Akademika, 2020)
There are many way to decrease Maternal Mortality Rate (MMR) in Indonesia. One of the efforts made antenatal care (ANC) integrated on a regular basis during pregnancy. The service quality affects the health of antenatal and fetal, maternal and newborn and postpartum mothers. Detection of high-risk pregnancy is important because every pregnancy is at risk of experiencing complications. The objective of this study was to detect high-risk pregnancy in an integrated ANC services. This was a cross sectional prospective study conducted on pregnant women in Puskesmas Bangkala on August, 2020. The research sample was taken by total sampling. The collection of data through observation with Puji Rochyati Score Card (KSPR) and documentation study from results ANC examination, laboratory and medical. Data were analyzed with descriptive analysis. The results of the 51 respondents obtained most (63%) had high-risk pregnancies (score 6-10) and a small portion (37%), low risk (score 2-6), most (67%) encountered a problem and a small proportion ( 33%) normal, a condition that troubled the majority (80%) of newly discovered when ANC integrated and a small portion (20%) cases of the old, the findings of a problem pregnancy is largely (55%) cases of obstetric, 25% of medical cases and 20% both. Detection of high risks remain important in integrated ANC. Detection of high risk carried out synergy with a series of checks on the mother as a detection problem or disease. Adequate intervention will help pregnant women in labor.